Electronic descriptors for designing high-entropy alloy electrocatalysts by leveraging local chemical environments - Guolin Cao; Sha Yang; Ji-Chang Ren; Wei Liu (Nature Communications)
Abstract High-entropy alloys (HEAs) present a vast compositional space for fine-tuning electrocatalytic activities, leveraging millions of distinct active sites on the surface. However, the intricate local chemical environment poses challenges to the rational and efficient design of HEA electrocatalysts with high reactivity. Here, focusing on noble-metal HEAs for oxygen reduction reactions, we propose a straightforward yet effective descriptor for quantitively determining the local reactivities of HEAs. This descriptor is based on a linear combination of the intrinsic d-band filling of the active center and the neighborhood electronegativity. Our model offers an accurate and robust description of the binding strengths of intermediates with different adsorption configurations on HEAs, supported by external density functional theory calculations. Importantly, the local environmental electronegativity of the HEA surface is strongly related to the d-band profile of the center atom(s) embedded within. Finally, we establish a library of activity maps for HEAs encompassing nine noble-metal elements, suggesting that Pd-rich and Ir-rich alloys, such as Pd–Ag, Ir–Pt, Ir–Au compositions, hold promise as potential candidates for optimal electrocatalysts.